VARIETAL REPLACEMENT IN THE EXPERIMENT “CONTINUOUS CULTIVATION OF WINTER RYE” - Biliavskyi, Yu.; Biliavska, L.; Sokyrko М. (Scientific Progress & Innovations, 2022)
The article provides the results of analysis of varietal composition of winter rye (Secale cereal L.) in a multi-year experiment “Constant cultivation of winter rye”, which has been conducted at the Poltava State Agricultural Research Station named after M.I. Vavilov of Institute of Pig Breeding and Agro - Industrial Production of NAAS for 137 years. The period of use of each individual variety in the experiment, the yield and its fluctuations during the cultivation period were shown. The variety remains the main factor in increasing crop yields. Varietal replacement is the replacement of one variety with another that better meets modern production requirements. It is carried out as new varieties are registered in order to increase yields and improve product quality. Recently, there has been a dynamic renewal of varietal composition of winter rye. The State Register of Plant Varieties Suitable for Distribution in Ukraine in 2021 includes 56 varieties and hybrids of this crop. The share of varieties of foreign selection gradually increased to 47%. However, today the varieties of Ukrainian selection are quite competitive. During the period of the experiment on the constant cultivation of winter rye used 9 varieties. The first in the experiment was the Probstein variety, which was sown for 23 years (1885 – 1907). The shortest period of use (3 years) was in the variety Poltavske (1908–1910), and the longest (50 years) was in the variety Petkusske (1911–1960) Since 1961, varietal replacement has been performed by varieties of breeding of the Plant Production Institute named after V. Ya. Yuriev of NAAS of Ukraine – Kharkivske 194 (1961–1964) Kharkivske 55 (1965–1982), Kharkivske 78 (1983–1992), Kharkivske 88 (1993–1998), Kharkivske 95 (1999–2009), Khamarka (2010–2021). Usually, varietal change in this experiment is carried out based on the results of production varietal testing in the station. Thus, in 2008–2009, among the new varieties of winter rye Kharkivske 95, Kharkivske 98, Hasto, Hamarka, Pervistok F1, Yurgivets F1, the best variety was Hamarka, which was used for the next 12 years. In 2022, it was decided to replace the Hamarka variety in Pamiat Khudoierko.